1992
DOI: 10.1530/acta.0.1270271
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wheat bran on blood and tissue hormone levels in adult female rats

Abstract: Arts CJM, Thijssen JHH. Effects of wheat bran on blood and tissue hormone levels in adult female rats.The protective effect of dietary fiber on breast cancer development might be explained by the interaction between dietary fiber and hormonal processes. We studied the effects of dietary fiber and the effects of a reduced energy intake on the exposure of mammary tissue to both estrogens and progesterone, as well as the blood plasma levels of these steroids and of LH and FSH. Adult female Fisher rats were fed ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Dietary fiber increases the fecal excretion of estrogen [11] and binds estradiol [12] thereby reducing bio-available levels; and most studies in humans have found that estrogen levels decrease as dietary fiber increases [17,19,[34][35][36][37]. Dietary fiber may also influence estrogen levels through its regulation of body weight.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary fiber increases the fecal excretion of estrogen [11] and binds estradiol [12] thereby reducing bio-available levels; and most studies in humans have found that estrogen levels decrease as dietary fiber increases [17,19,[34][35][36][37]. Dietary fiber may also influence estrogen levels through its regulation of body weight.…”
Section: Discussionmentioning
confidence: 99%